1990
DOI: 10.1111/j.1151-2916.1990.tb07620.x
|View full text |Cite
|
Sign up to set email alerts
|

Creep Deformation and the Grain‐Boundary Resistivity of Tetragonal Zirconia Polycrystalline Materials

Abstract: The grain-boundary resistivity of tetragonal zirconia polycrystals, which had undergone creep with different applied compressive loads and at different temperatures, has been measured with impedance spectroscopy. A stress exponent of unity was determined from strain rate versus stress data. The grain-boundary resistivity decreased significantly with increasing stress at a constant creep temperature indicating squeezing out of the glassy phase from interfaces between grains. This, however, had no effect on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 4 publications
1
15
0
2
Order By: Relevance
“…The activation energy does not vary if chemically different siliceous phases are present [25,28,29,[67][68][69][70], nor does it change if the siliceous phase is squeezed out [22]. Badwal et al [22] observed that the significant increase of the grain-boundary conductivity obtained in this way left the activation energy for the grain-boundary conductivity essentially unchanged. Therefore, the intergranular siliceous phase is expected to be poorly conductive or even insulating.…”
Section: Extrinsic Effect: Grain-boundary Impurity Phasementioning
confidence: 96%
See 1 more Smart Citation
“…The activation energy does not vary if chemically different siliceous phases are present [25,28,29,[67][68][69][70], nor does it change if the siliceous phase is squeezed out [22]. Badwal et al [22] observed that the significant increase of the grain-boundary conductivity obtained in this way left the activation energy for the grain-boundary conductivity essentially unchanged. Therefore, the intergranular siliceous phase is expected to be poorly conductive or even insulating.…”
Section: Extrinsic Effect: Grain-boundary Impurity Phasementioning
confidence: 96%
“…to form an intergranular siliceous phase. It is commonly accepted that the intergranular siliceous phase significantly affects the grain-boundary electrical properties of acceptor-doped ZrO 2 and CeO 2 [15,[17][18][19][20][21][22][23][24][25][26][27][28]30,31,38,40,47,[49][50][51]54,55,[61][62][63][64][69][70][71]. The intergranular siliceous phase is very dynamic in nature, the composition, location, viscosity and wetting properties change with the types and amounts of the impurities in starting powders, sintering atmospheres and temperatures, and cooling rates.…”
Section: Extrinsic Effect: Grain-boundary Impurity Phasementioning
confidence: 99%
“…The binary system Sc 2 O 3 ZrO 2 is complex and the true equilibrium phase diagram has still not been fully resolved. Since the early work of Thornber et al, 18) at least seven phases have been identified as forming in the zirconia-rich end of the phase diagram. More recent studies have continued to refine these phase regions.…”
Section: Introductionmentioning
confidence: 99%
“…El aumento de la conductividad de la frontera de grano en muestras deformadas y/o sometidas a alta temperatura ya ha sido observado por otros autores (11,12). En el caso de muestras sometidas a deformación, se atribuye el aumento de la conductividad a la mejora del contacto eléctrico entre los granos por la desaparición de impurezas que dificultan su buen contacto (11).…”
Section: Frontera De Granounclassified
“…En el caso de muestras sometidas a deformación, se atribuye el aumento de la conductividad a la mejora del contacto eléctrico entre los granos por la desaparición de impurezas que dificultan su buen contacto (11). El otro mecanismo que aumenta la conductividad de la frontera de grano es la eliminación de fase vítrea en el recocido (12). En nuestras muestras no hemos observado la existencia de fases vítrea por lo que pensamos que el mecanismo por el que ha aumentado la conductividad es la mejora del acoplamiento electrico entre los granos.…”
Section: Frontera De Granounclassified